Re-engineering teaching practice through reflexive practice and culturally relevant pedagogy framework - Pitsoe, Victor J.; Letseka, Matsephe M. (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
The shift towards Reflexive Practice and Culturally Relevant Pedagogy (CRP) in teaching practice is critical for the 21st century teachers. In this article, we argue that reflexive teaching and culturally relevant pedagogy frameworks qualify to be used for promoting student knowledge in the teaching practice. For us, teaching practice, as a social tool, is not at all an independent process, disconnected and apart from the society it serves. It is our contention that there is dire need to reengineer teaching practice within the poststructuralist framework. Among others, teaching practice in Open Distance Learning (ODL) setting should be realigned to embrace ethnic groups’ cultural values, traditions, communication, learning styles, contributions, and relational patterns. We hold that politics of resistance, counter-hegemonic struggle and emancipation can be brought through reflexive practice and culturally relevant pedagogy. In this article, we use Bourdieu’s concept of reflexivity and Ladson-Billings’ framework of Culturally Relevant Pedagogy as a conceptual tool to unpack a shift towards pedagogies of reflection in teaching practice.